(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of GA3 and SA on growth and yield of Limonium var. Misty Blue at Greenhouse Complex, Navsari Agricultural University, Navsari, during September 2014 to May 2015. The results indicate that application of salicylic acid (SA) @ 150 mg/lite recorded significantly higher plant height (20.95 cm), minimum days to flowering (84.07) with maximum inflorescence length (172.90 cm), whereas application of gibberellic acid (GA3) @ 200 mg/lite recorded significantly maximum number of shoots/plant (1.80), flowering duration (16.60 days), weight of inflorescence/plant (79.24 g), number of inflorescences/plant (5.93) and vase-life (6.13 days).